2014
DOI: 10.1097/dcr.0000000000000172
|View full text |Cite
|
Sign up to set email alerts
|

Dysplasia in Ulcerative Colitis as a Predictor of Unsuspected Synchronous Colorectal Cancer

Abstract: The presence of dysplasia was associated with a low risk of unsuspected cancer at the time of colectomy. These findings will help inform the decision-making process for patients with ulcerative colitis who are considering intensive surveillance vs surgical intervention after a diagnosis of dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…7, 21, 22, 28, 31-37 Overall, findings at time of surgery were: no dysplasia, 37% (95% CI, 29-47; 197/450; I 2 =42%), LGD, 34% (95% CI, 30-39; 153/450; I 2 =0%) or advanced neoplasia, 30% (95% CI, 21-41; 97/450; I 2 =59%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7, 21, 22, 28, 31-37 Overall, findings at time of surgery were: no dysplasia, 37% (95% CI, 29-47; 197/450; I 2 =42%), LGD, 34% (95% CI, 30-39; 153/450; I 2 =0%) or advanced neoplasia, 30% (95% CI, 21-41; 97/450; I 2 =59%).…”
Section: Resultsmentioning
confidence: 99%
“…21-23,27-31 Among these, 11 patients underwent surgery with curative intent. Overall, two patients died during follow-up, both related to CRC – one patient died due to metastatic CRC, and another following recurrence of CRC after initial curative surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Two cohort studies and one case series reported on the rates of prevalent cancer found in the surgical colectomy specimen resected soon after a pre‐operative diagnosis of visible HGD where 94% 28 to 100% 29,30 had not been endoscopically resected pre‐operatively. The prevalent cancer rate varied from 0% (n = 0/26), 28 20% (n = 1/5) 30 to 35.8% (n = 34/95) 29 . The studies with the highest prevalent cancer rates only included cases where the dysplasia was located within the extent of inflamed mucosa, rather than proximal to it 29,30 .…”
Section: Resultsmentioning
confidence: 99%
“…Two cohort studies reported prevalent cancer rates after a pre‐operative diagnosis of invisible HGD as 22.2% (n = 8/36) where the dysplasia was specified to be within inflamed mucosa 29 and 3.0% where it was not specified (n = 1/33) 28 . The pooled estimated cancer prevalence rate from all these studies was 11.4% (95% CI: 4.6%‐20.3%).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, more recent studies report lower progression of LGD and HGD to more advanced dysplasia or neoplasia, likely because of improved endoscopic visualization and resection. 63,64 Improved confidence in dysplasia visualization has resulted in experienced practitioners more frequently opting for endoscopic removal of dysplasia with close follow-up, as opposed to routinely recommending proctocolectomy. While definitive guidelines have not been established, professional societies have released position statements regarding dysplasia management.…”
Section: Dysplasia Managementmentioning
confidence: 99%